The Potential Role of Respiratory Motion Management and Image Guidance in the Reduction of Severe Toxicities Following Stereotactic Ablative Radiation Therapy for Patients with Centrally Located Early Stage Non-Small Cell Lung Cancer or Lung Metastases - Chi, Alexander; Nguyen, Nam Phong; Komaki, Ritsuko (Frontiers in Oncology, 2014)
Image guidance allows delivery of very high doses of radiation over a few fractions, known as stereotactic ablative radiotherapy (SABR). This treatment is associated with excellent outcome for early stage non-small cell lung cancer and metastases to the lungs. In the delivery of SABR, central location constantly poses a challenge due to the difficulty of adequately sparing critical thoracic structures that are immediately adjacent to the tumor if an ablative dose of radiation is to be delivered to the tumor target. As of current, various respiratory motion management and image guidance strategies can be used to ensure accurate tumor target localization prior and/ or during daily treatment, which allows for maximal and safe reduction of set up margins. The incorporation of both may lead to the most optimal normal tissue sparing and the most accurate SABR delivery. Here, the clinical outcome, treatment related toxicities, and the pertinent respiratory motion management/image guidance strategies reported in the current literature on SABR for central lung tumors are reviewed.